Peluang Penyelesaian Sengketa Lahan Penghuni Rumah Tanah Negara Melalui Alternative Dispute Resolution Land dengan Asas-Asas Hukum Penelantaran Tanah dan Penanganan Dampak Sosial Kemasyarakatan - Sukorina, Diana; Mayasari, Ana (ANTASENA: Governance and Innovation Journal, 2025)
Recent legal and social developments have seen a significant increase in disputes involving houses built on state land, both vertically and horizontally. These disputes typically arise from overlapping claims of ownership over state-owned properties that have been neglected in terms of maintenance, usage, and purpose. Such cases fall under complex civil land disputes and demand resolution approaches that extend beyond legal formalism to also account for community-level social impacts. Litigation processes often fail to deliver fair and sustainable outcomes due to their adversarial nature. Therefore, Alternative Dispute Resolution (ADR) methods—such as negotiation, mediation, and conciliation—offer a more constructive and inclusive pathway. The implementation of ADR in these disputes must adhere to fundamental principles of contract law, including the principle of freedom of contract, good faith, consensualism, pacta sunt servanda, and personality. Furthermore, dispute resolution strategies must integrate the legal principles governing land neglect and consider the broader social consequences affecting affected communities. This article explores the potential of ADR as a viable mechanism to resolve civil disputes over state land housing by harmonizing legal frameworks with societal needs. The objective is to foster a win-win solution that reinforces legal certainty while promoting social justice and inclusiveness for all stakeholders involved.